Inovasi Awal Pengembangan Wisata Berbasis Masyarakat di Lembang Saluallo, Kecamatan Sangalla Utara, Kabupaten Tana Toraja - Azril Tangke Sombolinggi; Rilva Toding Bua; Abdias Tandi Arrang (Jurnal Pengabdian Kepada Masyarakat, 2026)
Community-based tourism (CBT) is a tourism development approach that places local communities as the main actors in managing and utilizing tourism resources. This approach is considered important as it promotes tourism sustainability while improving community welfare. Lembang Saluallo, located in Sangalla Utara District, Tana Toraja Regency, has considerable natural and cultural tourism potential; however, it has not been optimally managed through a community-based tourism approach. Therefore, this community service activity aims to encourage early innovation in community-based tourism development through community assistance and capacity building. The community service program was conducted by involving local government officials and community members as primary partners. A participatory approach was applied through field observation, socialization, discussions, training, and community mentoring. The stages of the program included identifying tourism potential, increasing community understanding of CBT and sustainability principles, and formulating an initial concept for community-based tourism management. The results indicate an improvement in community understanding and participation in tourism management. The community has begun to identify local natural and cultural tourism potentials and has shown initiative in developing supporting tourism facilities through self-help activities. These findings demonstrate that participatory assistance is effective in enhancing community readiness as the main actor in tourism development. This community service activity is significant as an initial step toward establishing sustainable community-based tourism management in Lembang Saluallo. Keywords : community-based tourism, community empowerment, sustainable tourism, tourism